Lurbinectedin in small cell lung cancer - Manzo, Anna; Sforza, Vincenzo; Carillio, Guido; Palumbo, Giuliano; Montanino, Agnese; Sandomenico, Claudia; Costanzo, Raffaele; Esposito, Giovanna; Laudato, Francesca; Mercadante, Edoardo; La Manna, Carmine; Muto, Paolo; et al. (Frontiers in Oncology, 2022)
Few treatment options are available for patients with small cell lung cancer (SCLC) in progression after a first-line therapy. A novel therapeutic approach is represented by lurbinectedin, a synthetic derivative of trabectedin that works by inhibiting oncogenic transcription and promoting apoptosis in tumor cells. A phase II basket trial demonstrated the activity of lurbinectedin at the dose of 3.2 mg/m2 in patients with SCLC who had failed a previous chemotherapy, with a response rate of 35.2%, a median progression-free survival (mPFS) of 3.5 months, and a median overall survival (mOS) of 9.3 months. Common severe adverse events (grades 3–4) were hematological disorders, including anemia (9%), leukopenia (29%), neutropenia (46%), and thrombocytopenia (7%). On the basis of the positive results of this phase II study, on June 2020, lurbinectedin was approved by the Food and Drug Administration as second line for SCLC patients in progression on or after platinum-based therapy. The subsequent phase III trial comparing the combination of lurbinectedin plus doxorubicin vs. CAV (cyclophosphamide, Adriamycin, and vincristine) or topotecan did not demonstrate an improvement in overall survival, although the experimental arm showed a superior safety profile. Combinations of lurbinectedin with other drugs, cytotoxic agents and immune checkpoint inhibitors, are currently under investigation. The results of these studies should better define the optimal clinical application of lurbinectedin.